Coumarin as a chemical probe to evaluate efficiency of vortex – based hydrodynamic cavitation process. Issue 1 (February 2022) - Srinivas, N. Santosh; Ramanan, K. Kishore; Rayappan, John Bosco Balaguru; Kaleekkal, Noel Jacob; Jegadeesan, Gautham B.
Abstract: Direct quantification of hydroxyl radicals (OH ), the major driver for advanced oxidation process (AOPs), is difficult due to its high reactivity and extremely low half-life. Given that the effectiveness of AOPs is usually determined by its ability to generate hydroxyl or peroxyl radicals, a quantitative measurement of these radicals is essential to assess the performance of the process. In this study, for the first time, the performance of a vortex-based hydrodynamic cavitation (HC) system is evaluated via an indirect method using coumarin as a chemical probe. The hydroxylation of coumarin – an indirect indicator of OH - to 7-OHC served as a measure of the efficiency of the HC system. The inception of cavitation was observed at ΔP > 100 kPa, and maximum coumarin hydroxylation occurred at ΔP = 250 kPa, pH < pKa and in non-isothermal conditions. The maximum observed coumarin conversion with HC alone was 6%, with the cavitation yield of 3.87 × 10 −4 mg/W-min. The use of persulfate oxidant along with HC is the most effective in maximizing OH generation with a cavitation yield of 15.30 × 10 −4 mg/W-min. This study shows that simpler chemical probes such as coumarin can be used to identify the best-operating conditions across cavitating devices and can be used in their scale-up and comparison. Graphical Abstract: ga1 Highlights: Coumarin as a chemical probe for evaluating vortex-diode based HC system. Low ΔP, non-isothermal conditions and pH < pKa provided best OH radical generation. Optimized parameters validated using degradation results of other model pollutants. HC + persulfate process provided highest OH radical yield.